2014
DOI: 10.7860/jcdr/2014/7431.4016
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study Between Modified Bassini’s Repair and Lichtenstein Mesh Repair of Inguinal Hernias in Rural Population

Abstract: Background: Bassini's repair and the Lichtenstein's tension free mesh hernioplasty are commonly used hernia repair techniques and yet there is no unison as to which is the best technique. Our hospital being in a rural setup and catering to majority of poor patients who are daily wagers, open hernia repairs are commonly done. This study was undertaken to compare the technique and post-operative course so as to determine the best suitable of the two procedures for them. Materials and Methods:A comparative random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Wayne et al in their study on the use of the bassini repair in the treatment of inguinal hernias showed a recurrence rate of 3.7% to 4.8%, but they are much higher than the Lichtenstein repair. Another downside of this procedure is the need to avoid excessive tension over the inguinal region by not lifting heavy objects [32,33].…”
Section: Other Hernia Repairsmentioning
confidence: 99%
“…Wayne et al in their study on the use of the bassini repair in the treatment of inguinal hernias showed a recurrence rate of 3.7% to 4.8%, but they are much higher than the Lichtenstein repair. Another downside of this procedure is the need to avoid excessive tension over the inguinal region by not lifting heavy objects [32,33].…”
Section: Other Hernia Repairsmentioning
confidence: 99%